A nulling-resistor output amplifier in the framework of heterostructures based on nonlinear partial differential equations - Evgeny Leonidovich Pankratov (International Journal of Advances in Applied Sciences, 2022)
In this paper, we introduce an approach to increase the density of field-effect transistors framework nulling-resistor output amplifier. In the framework of the approach, we consider manufacturing the amplifier in a heterostructure with a specific configuration. Several required areas of the heterostructure should be doped by diffusion or ion implantation. After that dopant and radiation defects should be annealed framework optimized scheme. We also consider an approach to decrease the value of mismatch-induced stress in the considered heterostructure. We introduce an analytical approach to analyze mass and heat transport in heterostructures during the manufacturing of integrated circuits with account for mismatch-induced stress.